CHARACTERISTICS AND CLINICAL MANAGEMENT OF FEMALE PATIENTS WITH FISSURE IN ANO IN AL-KADHIMIYA CITY, BAGHDAD (Iraqi Journal of Medical Sciences, 2016)
Background:Fissure in ano is a common painful anal problem in female patients.Objective:To study the sociodemographic variables of female patients with fissure in ano, and to identified the characteristic of anal fissure and their treatment among those patient in Al-Imamian Al-Kadhimiyian Medical City and two private hospitals.Methods: This is a prospective study that was carried out from May 2008 to May 2011. Two hundred fifty female patients with fissure in ano were interviewed regarding their age, marital state, address, level of education, clinical presentation and the subsequent management.Result:The commonest age of presentation in females was between 21-30 years. 78% of them were living at the peripheral areas of north of Baghdad, and 79.6% were of low level of education (primary school or below). The prevalence was found more in women with high parity especially when their child delivery was supervised by a midwife in their location. All patient has presented with anal pain, 55% were associated with bleeding per rectum and 64.2% with constipation. The location of fissures was 51.6% anterior, 48% posterior, 0.4% lateral in position. Less than half of patients underwent a surgical treatment. 77% of them were treated by lord dilatation under anesthesia and 23% by lateral sphinecteromty.Conclusion:Factors which had an impact on the clinical course and management of fissure in ano in female patients were found to be the social status, the level of education and the parity, therefore to prevent this illness, a cooperation between the heath services and the family health center and the government is necessary in order to overcome such a common problem.Keywords:Fissure in ano, Female
Keywords: Fissure in ano; Female